Early appearance of developmental alterations in the dendritic tree of the hippocampal granule cells in the Ts65Dn model of Down syndrome. Issue 4 (19th January 2021) - Uguagliati, Beatrice; Al‐Absi, Abdel‐Rahman; Stagni, Fiorenza; Emili, Marco; Giacomini, Andrea; Guidi, Sandra; Nyengaard, Jens Randel; Bartesaghi, Renata
Abstract: Down syndrome (DS), a genetic condition caused by triplication of chromosome 21, is characterized by alterations in various cognitive domains, including hippocampus‐dependent memory functions, starting from early life stages. The major causes of intellectual disability in DS are prenatal neurogenesis alterations followed by impairment of dendritic development in early infancy. While there is evidence that the Ts65Dn mouse, the most widely used model of DS, exhibits dendritic alterations in adulthood, no studies are available regarding the onset of dendritic pathology. The goal of the current study was to establish whether this model exhibits early dendritic alterations in the hippocampus, a region whose function is severely damaged in DS. To this purpose, in Golgi‐stained brains, we evaluated the dendritic arborization and dendritic spines of the granule cells of the hippocampal dentate gyrus in Ts65Dn mice aged 8 (P8) and 15 (P15) days. While P15 Ts65Dn mice exhibited a notably hypotrophic dendritic arbor and a reduced spine density, P8 mice exhibited a moderate reduction in the number of dendritic ramifications and no differences in spine density in comparison with their euploid counterparts. Both in P8 and P15 mice, spines were longer and had a longer neck, suggesting possible alterations in synaptic function. Moreover, P8 and P15 Ts65Dn mice had more thin spines and fewer stubby spines in comparison with euploid mice. Our study provides novel evidence on the onset of dendritic pathology, one of the causes of intellectual disability in DS, showing that it is already detectable in the dentate gyrus of Ts65Dn pups. This evidence strengthens the suitability of this model of DS as a tool to study dendritic pathology in DS and to test the efficacy of early therapeutic interventions aimed at ameliorating hippocampal development and, therefore, memory functions in children with DS.